1999
DOI: 10.1046/j.1365-2621.1999.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of irradiated lamb meat with bone: effect of chilled storage and cooking on esr signal strength

Abstract: The effect of gamma-irradiation doses of 1, 2, 4 and 5 kGy on ESR signal intensity in pre-packed irradiated lamb meat chunks containing bones was studied. Irradiationinduced a characteristic ESR signal in bone that was not detected in non-irradiated samples and its intensity was proportional to irradiation dose up to 5 kGy. In samples irradiated to 2.5 kGy for shelf-life enhancement, ESR signal intensity was monitored immediately after irradiation and subsequently at weekly intervals during storage at 0-3 ЊC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…The ESR spectra of bone powder prepared from all samples were examined for the presence of a typical radiation induced signal with g⊥ = 2.0022 and g ll = 1.9976 (Desrosiers & Simic, 1988; Morehouse et al. , 1991; Chawla et al. , 1999, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESR spectra of bone powder prepared from all samples were examined for the presence of a typical radiation induced signal with g⊥ = 2.0022 and g ll = 1.9976 (Desrosiers & Simic, 1988; Morehouse et al. , 1991; Chawla et al. , 1999, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In India, irradiation treatment of meat and meat products (including chicken) up to 4 kGy has been permitted for domestic marketing and consumption by the Ministry of Health since April 1998. In our previous studies, we have demonstrated the practicality of ESR spectroscopy to detect irradiation treatment in bone‐in lamb meat chunks (Chawla et al. , 1999, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, a group of India scientists studied the effects of c-irradiation at dose levels of 1, 2, 4, and 5 kGy on ESR signal intensity in the lamb meat chunks with hind leg (femur) and rib bones [56]. They demonstrated that irradiation at 2.5 kGy generated detectable levels of free radicals in the lamb bones regardless of bone type, but the intensity of ESR signal was much higher in the hind leg bone than that in rib bone.…”
Section: Food Irradiation 61 Irradiated Meat Productsmentioning
confidence: 99%
“…Furthermore, the ESR signal intensity was stable for up to 7 months when 1 and 2 kGy irradiation was used to treat the lamb samples, whereas ESR signal intensity decreased at the storage time of 3 and 4 months for meat samples treated with 4 and 5 kGy irradiation. In addition, it was observed that ESR signal was still detectable after cooking and chilled storage, although conventional cooking procedures including boiling, pressure cooking, and microwaving, resulted in a reduction in ESR signal intensity in the cooked lamb meat products [56]. It was concluded that ESR spectroscopy is an effective technique for identifying irradiated lamb meat containing bone tissue, which were explored to an irradiation dose range of 2.5 -5.0 kGy and might have been stored and/or cooked [56].…”
Section: Food Irradiation 61 Irradiated Meat Productsmentioning
confidence: 99%
See 1 more Smart Citation